Carbon nanotube-based flexible high-speed circuits with sub-nanosecond stage delays - Guanhua Long; Jin, Wanlin; Fan Xia; Yuru Wang; Bai, Tianshun; Chen, Xingxing; Liang, Xuelei; Peng, Lian-Mao; Hu, Youfan (Nature Communications, 2022)
High-speed flexible circuits are required in flexible systems to realize real-time information analysis or to construct wireless communication modules for emerging applications. Here, we present scaled carbon nanotube-based thin film transistors (CNT-TFTs) with channel lengths down to 450 nm on 2-mu m-thick parylene substrates, achieving state-of-the-art performances of high on-state current (187.6 mu A mu m(-1)) and large transconductance (123.3 mu S mu m(-1)). Scaling behavior analyses reveal that the enhanced performance introduced by scaling is attributed to channel resistance reduction while the contact resistance (180 +/- 50 k omega per tube) remains unchanged, which is comparable to that achieved in devices on rigid substrates, indicating great potential in ultimate scaled flexible CNT-TFTs with high performance comparable to their counterparts on rigid substrates where contact resistance dominates the performance. Five-stage flexible ring oscillators are built to benchmark the speed of scaled devices, demonstrating a 281 ps stage delay at a low supply voltage of 2.6 V. High-speed flexible circuits are essential in flexible systems for real-time information analysis and wireless communication. Here, flexible circuits are reported with a 281 ps stage delay based on scaled carbon nanotube thin film transistors.